Bivariate extreme value analysis of extreme temperature and mortality in Canada, 2000-2020 ... - Zhang, Yuqing; Wang, Kai; Ren, Junjie; Liu, Yixuan; Ma, Fei; Li, Tenglong; Chen, Ying; Ling, Chengxiu (figshare, 2024)
Abstract Climate change increases the risk of illness through rising temperature, severe precipitation and worst air pollution. This paper investigates how monthly excess mortality rate is associated with the increasing frequency and severity of extreme temperature in Canada during 2000-2020. The extreme associations were compared among four age groups across five sub-blocks of Canada based on the datasets of monthly T90 and T10, the two most representative indices of severe weather monitoring measures developed by the actuarial associations in Canada and US. We utilize a combined seasonal Auto-regressive Integrated Moving Average (ARIMA) and bivariate Peaks-Over-Threshold (POT) method to investigate the extreme association via the extreme tail index $$χ$$ χ and Pickands dependence function plots. It turns out that it is likely (more than 10%) to occur with excess mortality if there are unusual low temperature with extreme intensity (all $$χ >0.1$$ χ > 0.1 except Northeast Atlantic (NEA), ...